SAMR as a framework for modeling of Academic Information System in higher education institution toward education 3.0 - Utomo, Hadi Prasetyo; Bon, Abdul Talib; Hendayun, Mokhamad (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The implementation of Education 3.0 in educational institutions, mainly in higher education institutions (HEIs) has been growing from day to day. The implementation of Education 3.0 has brought the institution towards better education. But on the other hand, the implementation also gives new problems to the institution. The problems are increased administrative processes, insufficient mobility access, and unavailability of access for parents and industry. The problems can be solved by using ICT tools that have been used in many educational institutions called academic information system (AIS). AIS can be used as a way out to overcome the problems mentioned above. To be used in support the Education 3.0, AIS must be transformed in accordance with the needs of Education 3.0. In the process of transforming an information system, a model is needed as a guide. This paper will discuss three models namely model-driven architecture (MDA), service-oriented architecture (SOA) and substitution-augmentation-modification-redefinition (SAMR) to find out which model best suits the characteristics of Education 3.0. At the end of the discussion, it can be concluded that SAMR is best suited to Education 3.0 characteristics.